2003
DOI: 10.1523/jneurosci.23-01-00203.2003
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Development of Forebrain Midline Glia and Commissural Projections inNfiaKnock-Out Mice

Abstract: Nuclear factor I (NFI) genes are expressed in multiple organs throughout development (Chaudhry et al., 1997; for review, see Gronostajski, 2000). All four NFI genes are expressed in embryonic mouse brain, with Nfia, Nfib, and Nfix being expressed highly in developing cortex (Chaudhry et al., 1997). Disruption of the Nfia gene causes agenesis of the corpus callosum (ACC), hydrocephalus, and reduced GFAP expression (das Neves et al., 1999). Three midline structures, the glial wedge, glia within the indusium gris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
237
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 207 publications
(255 citation statements)
references
References 54 publications
11
237
2
Order By: Relevance
“…At D24, pTEL progenitor clusters expressed slightly higher levels of MKI67 and GPC3, indicating these early populations are mitotically active (Filmus, 2001;Scholzen and Gerdes, 2000). By D54 and D100, pTEL progenitor clusters express NFIA and HOPX, consistent with a transition to astrogliogenesis and/or outer radial glial cell production (Deneen et al, 2006;Pollen et al, 2015;Shu et al, 2003;Thomsen et al, 2016). After D54, pMGE clusters also express higher levels of HOPX, in addition to AQP4, S100B, ANXA1, and S100A10 compared to earlier clusters.…”
Section: Scrna-seq Analysis Of In Vitro-derived Human Interneuronsmentioning
confidence: 86%
“…At D24, pTEL progenitor clusters expressed slightly higher levels of MKI67 and GPC3, indicating these early populations are mitotically active (Filmus, 2001;Scholzen and Gerdes, 2000). By D54 and D100, pTEL progenitor clusters express NFIA and HOPX, consistent with a transition to astrogliogenesis and/or outer radial glial cell production (Deneen et al, 2006;Pollen et al, 2015;Shu et al, 2003;Thomsen et al, 2016). After D54, pMGE clusters also express higher levels of HOPX, in addition to AQP4, S100B, ANXA1, and S100A10 compared to earlier clusters.…”
Section: Scrna-seq Analysis Of In Vitro-derived Human Interneuronsmentioning
confidence: 86%
“…Recently, NFia, NFib, and NFic genes have been disrupted in mice. NFia knock-out mice are characterized by dramatic neuroanatomical defects, whereas NFib is needed for both brain development and lung maturation (35,36). In contrast, disruption of NFic causes postnatal loss of molar roots (37).…”
Section: Discussionmentioning
confidence: 99%
“…An additional mechanism of guidance at the cortical midline occurs via transient neuronal populations that form the subcallosal sling and a cellular corridor for callosal axons to cross the midline (Shu et al, 2003b;Niquille et al, 2009). We stained sections from both KOs and WT littermates with antibodies against the transcription factor Nfia, which labels the subcallosal sling (Shu et al, 2003a) and found it to be intact in both Slc12a6…”
Section: ⌬18/⌬18mentioning
confidence: 99%